The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/cncr.20856
|View full text |Cite
|
Sign up to set email alerts
|

The association of body mass index and prostate‐specific antigen in a population‐based study

Abstract: BACKGROUNDRecent studies of men with prostate carcinoma suggest that obesity may be associated with more advanced‐stage disease and lower overall survival rates. One possible link between body mass index (BMI) and prostate carcinoma prognosis may be disease ascertainment. Prostate‐specific antigen (PSA) is widely used to screen for prostate carcinoma.METHODSThe authors examined the association between BMI and PSA in a population‐based study of 2779 men without prostate carcinoma. Between 2001 and 2004, these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
176
4
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 53 publications
19
176
4
3
Order By: Relevance
“…[1][2][3] Some have proposed this as a mechanism for later detection of prostate cancer in obese men. 8,9 As PSA is regulated by androgen, investigators have hypothesized that lower PSA concentration may result from decreased androgenic activity in obese men. 9,10 However, men with higher BMI also have larger plasma volumes, which could decrease serum concentration of soluble tumor markers-a phenomenon known as hemodilution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Some have proposed this as a mechanism for later detection of prostate cancer in obese men. 8,9 As PSA is regulated by androgen, investigators have hypothesized that lower PSA concentration may result from decreased androgenic activity in obese men. 9,10 However, men with higher BMI also have larger plasma volumes, which could decrease serum concentration of soluble tumor markers-a phenomenon known as hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 As PSA is regulated by androgen, investigators have hypothesized that lower PSA concentration may result from decreased androgenic activity in obese men. 9,10 However, men with higher BMI also have larger plasma volumes, which could decrease serum concentration of soluble tumor markers-a phenomenon known as hemodilution. 11 This explanation was validated by Branz and co-workers study on prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,23 Studies investigating the effects of BMI among men with elevated PSA consistent with biopsy referral have not shown a clear relationship. 9 Overall, the association between body size and PSA density appears to be attributable to the relationships between body size and prostate volume.…”
Section: Discussionmentioning
confidence: 99%
“…Increased prostate-specific antigen (PSA) testing 14,15 and somewhat lower blood PSA levels associated with BMI, 16,17 and differential prostate cancer detection with respect to obesity as mediated by effects on prostate volume may also contribute to inconsistencies in research investigating the association between obesity and prostate cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among the many factors that may affect blood PSA levels, such as age and race, BMI has been associated with lower PSA levels among apparently healthy men without a history of prostate cancer. [35][36][37] Indeed, PSA expression is under androgen receptor regulation, and obesity and hyperinsulinemia are also associated with lower testosterone levels. [38][39][40][41][42] However, a prior study found no association between leptin or adiponectin and PSA among prostate cancer patients, 43,44 and the component(s) of body adiposity as estimated by BMI that affect PSA levels and perhaps the ability to detect early-stage prostate cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%